The purchasing power argument: Could rising wages foster employment? - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2008)
The so-called purchasing power argument of wages (PPA), suggesting that rising wages could increase employment instead of reducing it, is examined within a general theoretical framework. While the demand side is modelled by means of a path-dependent Keynesian model with a Kaldorian saving function, a neoclassical production function is assumed on the supply side. It is shown that there is a core of truth in the PPA, if real wages are lower than marginal productivity of labour. While a temporary demand shock could indeed be overcome by rising wages, it is not possible, however, to outweigh a permanent slump in total demand by that way. Moreover, in contrast to conventional fiscal policy, wage rises according to the PPA imply both a rising price level and the danger of neoclassical unemployment. In an open economy, the relevance of the PPA is generally further reduced.
Keywords: 330